2001
DOI: 10.1080/09629350120093713
|View full text |Cite
|
Sign up to set email alerts
|

17β‐Estradiol promotes the synthesis and the secretion of annexin I in the CCRF‐CEM human cell line

Abstract: AIMS: Annexin I (ANXA1), a 37kDa member of the annexin family of Ca2+-binding and phospholipid-binding proteins, is particularly abundant in various populations of peripheral blood leukocytes. Since this protein modulates the anti-inflammatory actions of the steroid hormones, the purpose of this study was to investigate the effects of the female sex steroid hormone, 17beta-estradiol (E2beta), on the synthesis and secretion of ANXA1 in the human CCRF-CEM acute lymphoblastic leukemia cell line. METHODS: Compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…Moreover, a significant increase in the amount of ANXA1 excreted out of plasma membrane was also observed. It has been reported that the increase in the cellular turnover ofANXA1 may cause a rapid export of the proteins from intracellular stores to extracellular sites and as a consequence the de novo synthesis of proteins may took place to replenish the depleted intracellular levels [16]. Based on these findings, our results indicate that the investigated compounds may have a potential to efficiently stimulate the ANXA1 secretion.…”
Section: Discussionsupporting
confidence: 49%
“…Moreover, a significant increase in the amount of ANXA1 excreted out of plasma membrane was also observed. It has been reported that the increase in the cellular turnover ofANXA1 may cause a rapid export of the proteins from intracellular stores to extracellular sites and as a consequence the de novo synthesis of proteins may took place to replenish the depleted intracellular levels [16]. Based on these findings, our results indicate that the investigated compounds may have a potential to efficiently stimulate the ANXA1 secretion.…”
Section: Discussionsupporting
confidence: 49%
“…Some of the genes, such as annexin-1 and bcl-x, are known as estrogen-regulated genes (Castro-Caldas et al 2001, Stoltzner et al 2001. A few genes, including mitochondrial uncoupling protein 2 and platelet factor 4, which were regulated by E 2 in our study, have been previously described as estrogen insensitive in other tissues (Norris & Bonnar 1994, Luukkaa et al 2001, Stirone et al 2005.…”
Section: Discussionmentioning
confidence: 94%
“…This event could potentially explain the presence of structural proteins pulled down in our results. Interestingly, E2 can also modulate the expression of members of the annexin family (42,43), further supporting interplay between annexins and estrogen receptors. Taken together, these results suggest that protective aspects of E2 signaling could be mediated through estrogen receptor-ANXA interactions demonstrated here and in other reports (12,44,45), and unique to this study is an age-related change in some of these associations with ER␤.…”
Section: Discussionmentioning
confidence: 99%